Chat Transcripts in the Context of the COVID-19 Pandemic: Analysis of Chats from the AskAway Consortia - Sobol, Barbara; Goncalves, Aline; Vis-Dunbar, Mathew; Lacey, Sajni; Moist, Shannon; Jantzi, Leanna; Gupta, Aditi; Mussell, Jessica; Foster, Patricia L.; James, Kathleen (Evidence Based Library and Information Practice, 2023)
Objective – During the COVID-19 pandemic, the majority of post-secondary institutions in British Columbia remained closed for a prolonged period, and volume on the provincial consortia chat service, AskAway, increased significantly. This study was designed to evaluate the content of AskAway transcripts for the 2019-2020 and 2020-2021 academic years to determine if the content of questions varied during the pandemic.Methods – The following programs were used to evaluate the dataset of more than 70,000 transcripts: R, Python (pandas), Voyant Tools and Linguistic Inquiry and Word Count (LIWC).Results – Our findings indicate that the content of questions remained largely unchanged despite the COVID-19 pandemic and the related increase in volume of questions on the AskAway chat service.Conclusion – These findings suggest that the academic libraries covered by this study were well-poised to provide continued support of patrons through the AskAway chat service, despite an unprecedented closure of physical libraries, a significant increase in chat volume, and a time of global uncertainty.